2021
DOI: 10.3390/cancers13123040
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular and Biological Impact of Extracellular Vesicles in Pancreatic Cancer

Abstract: Deciphering the interactions between tumor and stromal cells is a growing field of research to improve pancreatic cancer-associated therapies and patients’ care. Indeed, while accounting for 50 to 90% of the tumor mass, many pieces of evidence reported that beyond their structural role, the non-tumoral cells composing the intra-tumoral microenvironment influence tumor cells’ proliferation, metabolism, cell death and resistance to therapies, among others. Simultaneously, tumor cells can influence non-tumoral ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 157 publications
0
6
0
Order By: Relevance
“…THP-1 monocytes were harvested at a number of 5 × 10 5 /mL, differentiated in macrophages M0, treated with PC EVs and then analyzed for CD80, CD86, CD206 and CD163 expressions as reported in [32]. The pellets were incubated for 1 h at room temperature (RT) in PBS 1x containing FBS (2% v/v) and antihuman antibody against CD80, CD86, CD206, CD163 (1:100, Santa Cruz Biotechnologies, Dallas, TX, USA) and then for another hour with conjugated secondary antibody (1:100, antimouse).…”
Section: Flow Cytometrymentioning
confidence: 99%
See 2 more Smart Citations
“…THP-1 monocytes were harvested at a number of 5 × 10 5 /mL, differentiated in macrophages M0, treated with PC EVs and then analyzed for CD80, CD86, CD206 and CD163 expressions as reported in [32]. The pellets were incubated for 1 h at room temperature (RT) in PBS 1x containing FBS (2% v/v) and antihuman antibody against CD80, CD86, CD206, CD163 (1:100, Santa Cruz Biotechnologies, Dallas, TX, USA) and then for another hour with conjugated secondary antibody (1:100, antimouse).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…These latter (40-100 nm diameter) are small membranous extracellular vesicles (EVs) released from nonmalignant and malignant cells in the extracellular space and body fluids [21,[25][26][27][28][29][30]. EVs play a central role promoting cell-to-cell communication, cell proliferation, migration and invasion and are involved in organizing premetastatic niches as key modulators of the tumor microenvironment [24,[31][32][33][34][35]. Moreover, previous studies have shown that vesicles regulate the interactions between tumor and immune cells, such as TAMs [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 3D-cultured Schwann cells treated with TEVs (1000 TEVs per Schwann cell) show significant changes in their GFAP to S100 versus both monolayer- ( p < 0.005) and untreated 3D-cultured Schwann cells ( p < 0.0001). Elevated GFAP levels in mature Schwann cells in vivo is correlated with activation following pathophysiological events, such as peripheral nerve injury and cancer invasion. ,, While this relationship has been speculated, there exists limited evidence that TEVs modulate the Schwann cell activation necessary for the onset of perineural invasion . Future studies will investigate specific mechanisms of TEV-mediated Schwann cell activation in cancer settings.…”
Section: Results and Discussionmentioning
confidence: 99%
“…79,80,85 While this relationship has been speculated, there exists limited evidence that TEVs modulate the Schwann cell activation necessary for the onset of perineural invasion. 86 Future studies will investigate specific mechanisms of TEV-mediated Schwann cell activation in cancer settings. Changes to cell behavior in 2D versus 3D is also evident in dorsal root ganglia neurite cultures, signifying an important characteristic this hydrogel achieves to act as a biomimetic testbed.…”
Section: Resultsmentioning
confidence: 99%